Limb-girdle muscular dystrophy type 21 is not rare in Taiwan - Liang, Wen-Chen; Hayashi, Yukiko K.; Ogawa, Megumu; Wang, Chien-Hua; Huang, Wan-Ting; Nishino, Ichizo; Jong, Yuh-Jyh (My University, 2013)
Alpha-dystroglycanopathy is caused by the glycosylation defects of a-dystroglycan (alpha-DG). The clinical spectrum ranges from severe congenital muscular dystrophy (CMD) to later-onset limb girdle muscular dystrophy (LGMD). Among all alpha-dystroglycanopathies, LGMD type 21 caused by FKRP mutations is most commonly seen in Europe but appears to be rare in Asia. We screened uncategorized 40 LGMD and 10 CMD patients by immunohistochemistry for alpha-DG and found 7 with reduced a-DG immunostaining Immunoblotting with laminin overlay assay confirmed the impaired glycosylation of a-DG. Among them, five LGMD patients harbored FKRP mutations leading to the diagnosis of LGMD2I. One common mutation, c.948delC, was identified and cardiomyopathy was found to be very common in our cohort. Muscle images showed severe involvement of gluteal muscles and posterior compartment at both thigh and calf levels, which is helpful for the differential diagnosis. Due to the higher frequency of LGMD2I with cardiomyopathy in our series, the early introduction of mutation analysis of FKRP in undiagnosed Taiwanese LGMD patients is highly recommended. (C) 2013 Published by Elsevier B.V.
Keywords: Alpha-dystroglycan; Alpha-dystroglycanopathy; Limb-girdle muscular dystrophy type 21; FKRP; Dilated cardiomyopathy; Glycosylation defect; Laminin binding; Muscle imaging